(untitled) (Al-Academy, 2019)
The mark at the Children’s Theater did not receive as much attention as in the adult theater, despite the great attention given to its visual system, but some of the directors of the Children’s Theater approached the application of the same system of marking in the adult theater, without limiting a certain mechanism that identifies the mechanisms of mark operation and the modalities of its transformation in the visual display system, which called on the researcher to shed light in this study on the scientific shift in the visual display system and its functions in the children’s theater. The researcher formulated a title for his research (the mark transformation of the visual display system in the children’s theater) where the researcher identified the mark transformation in the visual system of the theater of the child as a goal for his research, and his study included four chapters, the first chapter stated the problem of research and the need for it, its importance, objectives, limits, and identified its terms and defined them procedurally. Chapter two constituted a theoretical framework for the study, including two sections, the first touched on the mark transformation, its functions, and applications in the field of theater, and the second section included the operating system of the visual system in the child’s theater. The second chapter reviews the indicators resulting from the theoretical framework The third chapter, which included the research procedures, where the researcher chose his sample (I am the lion) in a deliberate way using the descriptive method in the analysis, and concluded by discussing the main results of the analysis of the sample, which resulted in a set of conclusions and recommendations and the researcher concluded his research with reference to sources, references and research summary in English